Reassessment of the concept of Calomera decemguttata (Fabricius) with a description of Calomera paradecemguttata sp. nov. (Coleoptera: Cicindelidae) - Moravec, Jiří; Dheurle, Charles; Schüle, Peter; Wiesner, Jürgen (Zootaxa, 2025)
A taxonomic and nomenclatorial revision of the Calomera decemguttata species-complex within the tiger beetle genus Calomera Motschulsky, 1862 is presented. The revision has revealed that the genuine type of Cicindela decemguttata Fabricius, 1801 is not conspecific with the species commonly treated in literature as Calomera decemguttata. As a result, Calomera paradecemguttata sp. nov. (= C. decemguttata sensu auctorum, partim) is described as new to science. Differential diagnoses and a key to the members of the species-complex consisting of Calomera decemguttata Fabricius, 1801, C. durvillei (Dejean, 1831), C. mamasa Cassola & Brzoska, 2008, C. jakli Schüle, 2010, C. cabigasi Cassola, 2011, C. bordonii Wiesner, 2018 and C. paradecemguttata sp. nov. are presented. Two additional species, immediately differentiated from the C. decemguttata species-complex, yet obviously belonging to the same species-group, are also treated here: C. marmorata (W. Horn, 1925) (originally described as a subspecies of C. decemguttata) with differential diagnosis, lectotype designation and illustrations, and C. sanguineomaculata (Blanchard, 1853) with only differential diagnosis and note to C. sanguineomaculata savoensis (Cassola, 1987). Habitus and diagnostic characters are illustrated in colour photographs (those of type specimens of C. decemguttata, C. mamasa and C. marmorata are presented for the first time). Lectotype of Cicindela decemguttata is newly designated.